2018
DOI: 10.1186/s13071-018-2902-9
|View full text |Cite
|
Sign up to set email alerts
|

Babesia vesperuginis in insectivorous bats from China

Abstract: BackgroundTo increase understanding of human bacterial and parasitic pathogens in bats, we investigated the prevalence of Babesia spp., Rickettsia spp., Anaplasma spp. and Coxiella burnetii in bats from China.MethodsBats were captured from Mengyin County, Shandong Province of China using nets. DNA was extracted from the blood and spleen of bats for molecular detection of Babesia spp., Rickettsia spp., Anaplasma spp. and Coxiella burnetii with specific primers for each species.ResultsA total of 146 spleen sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Admittedly, most discussions of bat pathogen tolerance have been limited to Old World fruit bats [7, 8], distinct from the insectivorous bat hosts of B. vesperuginis. Babesia vesperuginis has been identified in bats across Europe [911], the Americas [12] and China [13, 14]; such widespread host and geographical ranges suggest, contrary to popular dogma, that infection-associated pathology is unlikely to be severe.…”
Section: Introductionmentioning
confidence: 99%
“…Admittedly, most discussions of bat pathogen tolerance have been limited to Old World fruit bats [7, 8], distinct from the insectivorous bat hosts of B. vesperuginis. Babesia vesperuginis has been identified in bats across Europe [911], the Americas [12] and China [13, 14]; such widespread host and geographical ranges suggest, contrary to popular dogma, that infection-associated pathology is unlikely to be severe.…”
Section: Introductionmentioning
confidence: 99%
“…Lima et al (2012) found Trypanosoma erneyi in African bats. Han et al (2018) reported that insectivorous bats were infected by Babesia vesperuginis, also Schaer et al (2013) The results of this study identified three species of bats, namely Hipposideros species, Taphozous species, and Eonycteris spelaea, in three caves on Lombok Island. The present study also documented five species of blood-sucking flies including Eucampsipoda sundaica, Megastrebla nigriceps Brachytarsina species, Stylidia cf.…”
Section: Resultsmentioning
confidence: 60%
“…Species of bats, such as Hipposederos bicolor, Eonycteris speleae, and Taphozous achates have been recently identified from bat caves in Lombok Island (Agustin et al, 2019). Han et al (2018) reported that 13.3% of 107 insectivorous bats were infected by Babesia vesperuginis. Several years before that, Schaer et al (2013) documented that Plasmodium species.…”
Section: Introductionmentioning
confidence: 99%
“…foi identificado na pesquisa por proteobactérias da família Anaplasmataceae, em que não houve amplificação de fragmentos parciais de DNA em nenhuma das amostras incluídas neste estudo, em consonância com literatura disponível sobre o tema, já que artigos científicos publicados por grupos em diferentes regiões do mundo demonstram baixa prevalência ou ausência da infecção por Anaplasma/Erlichia spp. em quirópteros e seus ectoparasitas (LOFTIS et al, 2005;SOCOLOVSCHI et al, 2012;REEVERS, et al, 2016;CICUTRIUM et al, 2017;HAN et al, 2018;LV et al, 2018;SZUBERT-KRUSZYŃSKA et al, 2019).…”
Section: Discussão Detecção De Membros Da Família Rickettsiaceaeunclassified